2, 4-Toluene diisocyanate detection in liquid and gas environments through electrochemical oxidation in an ionic liquid. Issue 4 (14th January 2016) - Lin, Lu; Rehman, Abdul; Chi, Xiaowei; Zeng, Xiangqun
Abstract : The electrochemical oxidation of 2, 4-toluene diisocyanate (2, 4-TDI) in an ionic liquid (IL) has been systematically characterized to determine plausible electrochemical and chemical reaction mechanisms and to define the optimal detection methods for such a highly significant analyte. Abstract : The electrochemical oxidation of 2, 4-toluene diisocyanate (2, 4-TDI) in an ionic liquid (IL) has been systematically characterized to determine plausible electrochemical and chemical reaction mechanisms and to define the optimal detection methods for such a highly significant analyte. It has been found that the use of an IL as the electrolyte allows the oxidation of 2, 4-TDI to occur at a less positive anodic potential with no side reactions as compared to traditional acetonitrile based electrolytes. UV-Vis, FT-IR, cyclic voltammetry and Electrochemical Impedance Spectroscopy (EIS) studies have revealed the unique mechanisms of dimerization of 2, 4-TDI at the electrode interface by self-addition reactions, which can be utilized to improve the selectivity of detection. The study of 2, 4-TDI redox chemistry further facilitates the development of a robust amperometric sensing methodology by selecting a hydrophobic IL ([C4 mpy][NTf2 ]) and by restricting the potential window to only include the oxidation process. Thus, this innovative electrochemical sensor is capable of avoiding the two most ubiquitous interferents in ambient conditions ( i.e. humidity and oxygen), thereby enhancing the sensor performance and reliability for real world applications. The method was established to detect 2, 4-TDI in both liquid and gas phases. The limits of detection (LOD) values were 130.2 ppm and 0.7862 ppm, respectively, for the two phases, and are comparable to the safety standards reported by NIOSH. The as-developed 2.4-TDI amperometric sensor exhibits a sensitivity of 1.939 μA ppm −1 . Moreover, due to the simplicity of design and the use of an IL both as a solvent and non-volatile electrolyte, the sensor has the potential to be miniaturized for smart sensing protocols in distributed sensor applications.